Pembuatan dan Perbaikan Modul Training Printing Processing di PT âXâ - Ngono, Sonya Nikita; Y.A., Debora Anne (Jurnal Titra, 2014)
âXâ Corporation always improve the quality and performance of all employees with provide training program. Training program that implemented at âXâ Corporation based by Best Training Practice (BTP) method. One of the tools that are used in training is training module. Training modules must comply with criteria, that is have a cover, revision sheets, table of contents, objectives, programs, criteria, lesson plan, knowledge about operating a production process, and headers and footers that have been set by the company. Training module at Printing Processing, a total of six training modules are made and nine training modules are improved. Create and revision training module for Printing Processing that based by Best Training Practice (BTP) method be expected to support the training to attain an effective and efficient training.